Strategies utilized by plants to defend against Ralstonia solanacearum - Xue, Dexing; Wu, Weifeng; Kong, Danyu (Frontiers in Plant Science, 2025)
Ralstonia solanacearum, the causal agent of bacterial wilt, is recognized as one of the most destructive vascular pathogens. Plant defense responses are gradually developed through long-term interactions with R. solanacearum. The plant cell wall integrity (CWI) system has evolved to initiate defense responses via a diverse array of plasma membrane-resident sensors. These defense responses result primarily from physical and chemical actions that counteract infection with R. solanacearum. The plant cell wall serves as a defensive barrier against the pathogen, including cellulose, hemicellulose, pectin, lignin, and suberin. Various modifications to the cell wall and multiple changes in its composition are employed by plants resistant to R. solanacearum. Physical confinement vertically or horizontally induced in xylem tissues is the most effective method of defense against R. solanacearum. The timely formation of tyloses and gels within the vessel lumen contributes to the suppression of R. solanacearum. In addition, the deposition of callose at the infected sites reinforces the cell wall, thereby preventing the further spread of R. solanacearum. Morphological modifications, such as the thickening of the pit membranes and the increased number of larger xylem vessels, play crucial roles in conferring resistance to R. solanacearum. Secondary metabolites act as phytoalexins used by plants against R. solanacearum. In this review, we discuss the strategies deployed by plants resistant to R. solanacearum. In particular, we outline the physical and chemical restrictions, as well as the tissue constraints, against the vascular pathogen.